THE DEGREE OF COMMITMENT AND AWARENESS OF SCHOOLCHILDREN ON ASPECTS OF HEALTHY NUTRITION - Марина Юрьевна Галактионова; Наталья Владимировна Тихонова; Ольга Юрьевна Кутумова (The Publishing House Medicine and Enlightenment, 2024)
The aim of the research - assessment of the degree of commitment of children and adolescents to proper nutrition and the level of awareness of schoolchildren and their parents on aspects of rational nutrition. Materials and methods. The following methods were used: analytical, statistical (logical analysis), sociological. A survey was conducted of 240 schoolchildren (51.7 % of girls and 48.3 % of boys) and their parents in the period from February to April 2022 on the basis of the MAO «Secondary School N 149» in Krasnoyarsk, an experimental site of the Ministry of Health of the Krasnoyarsk Territory «Center for Promoting the Health of Schoolchildren». The study was conducted by a continuous survey of schoolchildren in grades 5-11. Results. Schoolchildren are sufficiently informed about healthy nutrition - 78.8 ± 2.3 %, but only 53.3 % adhere to a proper diet. At the same time, 14.6 % of schoolchildren eat 1-2 times a day, 9.2 % - «when they want», 5 % - 7-8 times. The majority of schoolchildren (63.3 %) have breakfast at home, the rest skip the first meal. Every third student is not satisfied with the quality of cooking, and 46.5 % of respondents are not satisfied with the menu offered in the school cafeteria. The diet includes a large amount of fats and fast-digesting carbohydrates. Conclusion. Thus, the data obtained provide the basis for the development of modern organizational and educational approaches to healthy nutrition of schoolchildren. First of all, it is necessary to take into account the research data when preparing menus in school canteens. To inform schoolchildren and family members, carry out educational work during the class hour within the framework of master classes and involve employees of psychological, pedagogical and medical specialties in this.